First records of ergasilus cerastes (Copepoda. poecilostomatoida) on cage- reared ictalarus from northeast Mexico - Rodríguez Almaraz, Gabino Adrián; Gómez Flores, Ricardo Alberto; Rábago Castro, Jaime Luis (Brill, 2012)
Copepods are a common component of the ectoparasitic assemblages of all kinds of fish, from all environments and ecosystems (Boxshall & Halsey, 2004). The family Ergasilidae comprises the most common parasites of freshwater fish and the highest diversity is found in the genus Ergasilus Von Nordmann, 1832, with more than 180 nominal species (El-Rashidy & Boxshall, 2001; Montú & Boxshall, 2002; Boxshall & Halsey, 2004). Ergasilus has a worldwide distribution except in Antarctica (Boxshall & Defaye, 2008; Thatcher & Brasil-Sato, 2008), inhabiting estuarine and freshwater ecosystems. Only the females are found on their fish hosts, whereas the males are free-living in the zooplankton (Amado et al., 1995; Suárez-Morales & Santana-Piñeros, 2008; Thatcher & Brasil-Sato, 2008).